An Emotion System Theory to address gaps in Affective Intelligence Theory and conceptualization of emotional phenomena - Roseman, Ira J. (Frontiers in Political Science, 2025)
How can emotions, and their influence on individuals and groups, be best conceptualized and studied by political scientists as well as by psychologists? Empirical work indicates that psychological theories, and research conducted by psychologists about emotions, are not only relevant but indeed important for understanding and predicting political phenomena. Building on a recent article by George Marcus, gaps are identified in Affective Intelligence Theory (AIT) and other theories of emotion that Marcus reviews, and an alternative, more comprehensive theory is delineated. The Emotion System Theory, here referred to as EST, encompasses a wider range of emotions and emotion-eliciting appraisals, and makes predictions differing from those in AIT about the determinants of political processes and specific political behaviors. For example, as distinct from AIT's focus primarily on enthusiasm, fear, and anger EST (a) defines and distinguishes among 16 positively- or negatively-valenced emotions plus the neutral-valenced emotion of surprise; (b) proposes five ways in which they can be measured; (c) specifies distinctive causes and components for each emotion; and (d) discusses their wide-ranging and often powerful impact e.g., on political information processing, communication (e.g., in campaigns and ads), candidate evaluation, voting, and various types of political participation. Together, these emotions constitute a coherent set of general-purpose response strategies for coping with crises and opportunities, within and outside of the political domain.